PENGARUH ORIENTASI ALKES TERHADAP ADAPTASI ANAK USIA SEKOLAH YANG MENJALANI HOSPITALISASI PERTAMA - Ni Wayan Sawitri (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
Hospitalization is a state of crisis in children when a child is ill and hospitalized. Children Adaptation of hospitalization consist of experience various aspects of hospital care including invasive procedures for diagnostic testing, pain,